Sequential Production of Levulinic Acid and Supercapacitor Electrode Materials from Cassava Rhizome through an Integrated Biorefinery Process - Gittisak Phachwisoot (2022)
In this study, thesequential production of levulinic acid (LA) and supercapacitor electrode materials from cassava rhizome (CR) was investigated through an integrated biorefinery process. The CR was pretreated in KOH solution at 120 °C for 1 h before valorization to LA via a catalytic hydrothermal process in 0.1-0.7 M HCl solution at 150-200 °C for 1-3 h. The maximum LA yield (19.62 wt %) was obtained under experimental conditions of 200 °C for 1 h in 0.4 M HCl. Thereafter, the hydrochar coproduct was further converted into porous activated carbon (AC) for use in supercapacitor electrodes. The AC was produced through a chemical activation process at 800 °C for 2 h using ZnCl2 and melamine as an activating agent and nitrogen source, respectively. The best AC sample for producing electrodes was obtained when using a hydrochar/ZnCl2/melamine ratio of 1:3:1. This species had the maximum specific capacitance (SC) of 192.5 and 173.0 F g-1 for three-and two-electrode systems, respectively. Moreover, the electrode material exhibits excellent cycling stability without a reduction in SC over 10,000 cycles at 1 A g-1 current density.